Hollow viscus injury due to blunt abdominal trauma - Varma Gunturi, Surya Ramachandra; Thumma, Venu Madhav; Bathalapalli, Jagan Mohan Reddy; Kunduru, Nava Kishore; Bishnoi, Kamal Kishore; Rakesh, Nirjhar Raj; Gondu, Gangadhar; Sarma, Digvijoy; Nagari, Bheerappa (International Surgery Journal, 2017)
Background: Management of hollow viscus injury (HVI) due to blunt abdominal trauma (BAT) is a challenge to the clinicians even in the era of advanced imaging and enhanced critical care. Repeated clinical examination with appropriate imaging with multidisciplinary teamwork is the key for timely intervention in equivocal cases for successful outcomes. Aim of the study was to present our experience over last 4½ years. Methods: This is a retrospective study of prospectively collected data of patients treated at surgical gastroenterology department, Nizam’s Institute of Medical Sciences, Hyderabad, India over a period of 4½ years (2012-2016). Results: A total of 126 BAT Patients were treated in our unit as inpatients during the last 4½ years. Out of 126, twenty patients (15.87%) with HVI in whom surgical intervention was done formed the study group. Contrast enhanced CT Scan abdomen and chest was done in stable patients (13/20), in rest of the patients (7/20) the decision to operate was taken more on clinical grounds along with X-ray abdomen and USG abdomen features. 12 (60%) had jejunal and ileal injuries, 5 (25%) patients had colonic injuries (sigmoid 4, caecum 1). One (5%) patient had extra peritoneal rectal perforation with ascending retroperitoneal fascitis and 2 (10%) had duodenal injury. Two (10%)patients required relaparotomy. We had mortality in 3 (15%) patients and 17 (85%) patients had complete recovery. Conclusions: Hollow viscus injury should be suspected in all cases of blunt abdominal trauma. In equivocal cases careful repeat clinical examinations with close monitoring and repeat imaging is highly essential to prevent delay in intervention. Type of procedure is based on time of presentation, degree of contamination, associated injuries and general condition of the patient.